Studies in symbolic interaction. - Denzin, Norman K. (Emerald, 2010)
Part I of Volume 34 of Studies in Symbolic Interaction contains 11 outstanding contributions by leading activist scholars on commodity racism, Chief Illiniwek, and native American sport mascots. Part II, New Interpretative Works, contains seven performance narratives: black womanhood, masculinity, whiteness, and gender, sexual violation, old civilization and democratic citizenship.